Meningkatkan Kecerdasan Sosial Emosional Anak Usia Dini Melalui Kegiatan Bercerita - Tiara Riffiana; Desvi Wahyuni (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This article explains the social emotional intelligence of early childhood through storytelling activities. Children with good emotional intelligence are children who are able to manage their emotions wisely through storytelling activities. In the storytelling process the teacher makes social emotional observations and assessments through storytelling. The assessment can be based on the child's attitude in storytelling activities, the child's reactions and oral tests related to the story. In terms of content, the method used in this article uses the literature study research method. The research results show that the series of books used by teachers include the book series for managing emotions (I Don't Sulk, I Don't Hit, I Don't Bite, I Don't Yell, I Don't Cry), types of emotions (When I'm Angry, When I'm Sad, When I'm Happy). Children can label what they feel and know how to convey it from stories related to emotions. So teachers use stories to help children's emotional development tasks.